Role of Phosphorus-Containing Molecules on the Formation of Nano-Sized Calcium Phosphate for Bone Therapy - Jiang, Yingying; Tao, Yali; Chen, Yutong; Xue, Xu; Ding, Gangyi; Wang, Sicheng; Liu, Guodong; Li, Mengmeng; Su, Jiacan (Frontiers in Bioengineering and Biotechnology, 2022)
Calcium phosphate (CaP) is a kind of the principal inorganic constituent of bone and teeth in vertebrates, and has realized various applications in the biomedical areas. Among various types of CaP, the amorphous calcium phosphate (ACP) is considered to have superior bioactive and with biodegradability. With regard to the instability of ACP, the phosphorus-containing molecules are usually adopted to solve this issue, but the specific roles of the molecules on the formation of nano-sized CaP have not been clearly clarified yet. Herein, the alendronate, cyclophosphamide, zoledronate and foscarnet are selected as the model molecules, and theoretical calculations were performed to elucidate the interaction between calcium ions and different model molecules. Subsequently, the CaPs were prepared with the addition of the phosphorus-containing molecules. It is found that cyclophosphamide has limited influences on the generation of CaP due to their weak interaction. During the co-precipitation process of Ca2+ and PO43-, the competitive relation among alendronate, zoledronate and foscarnet plays critical roles in the produced inorganic-organic complex. Besides, the biocompatibility of CaPs is also systematically evaluated. The DFT calculation provides a convincing strategy on predicating the structure of CaPs with various additives. This work is promising for designing CaP-based multifunctional drug delivery systems and tissue engineering materials.